Malaguerra: The anti-state super-hero of Sicilian Puppet Theater (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2020)
Although this literary figure is little known today, Morbello/Malaguerra was famous in Sicily and elsewhere in Italy from the mid-19th to mid-20th century. This essay focuses on his vicissitudes in print (Storia dei paladini di Francia) and on the puppet theater stage, with some attention to the spread of his name and adaptation of his adventures outside Sicily, both in the epic Maggio tradition of northern Italy and in the scripts of a Catanese puppeteer active in New York City. Because Malaguerra repeatedly contests the injustices perpetrated by those in power, his story reminds us that l’opera dei pupi was not simply a chivalric soap opera for the masses before television, but could be a vehicle to express a critical attitude toward the State under the cover of dramatizing medieval and Renaissance epics. Indeed, it may be that puppet theater’s political undercurrent was a factor in its massive popularity both in southern Italy and among Italian immigrants in urban centers of the New World. More generally, the essay aims to contribute to the discussion of political ideologies in the chivalric epic genre, especially in the context of Italian popular culture.